Charge‐ and Size‐Complementary Multimetal‐Induced Morphology and Phase Control in Zeolite‐Type Metal Chalcogenides. Issue 42 (27th June 2018) - Chen, Xitong; Bu, Xianhui; Wang, Yuan; Lin, Qipu; Feng, Pingyun
Abstract: Zeolite‐type chalcogenides are desirable due to their integration between porosity and semiconductivity. CPM‐120, with super‐sodalite topology (Zeolite Structure Code: RWY), is among the few zeolite‐type chalcogenides with permanent porosity, and is the only chalcogenide with a zeolite code. Importantly, the RWY‐type has evolved into a platform for studying properties of porous chalcogenides. Yet so far, few studies have been made to probe the effects of synthetic parameters and framework compositions on this platform. Here, we probe the effects of the third metal type (Ga 3+, In 3+, Cd 2+, and Sn 4+ ) on the Zn 2+ /Ge 4+ /S 2− platform. We find that charge‐complementary and size‐compatible Ga 3+ leads to the synthesis of CPM‐120‐ZnGaGeS which is the first trimetallic zeolite‐type chalcogenide, with improved crystal morphology and reproducibility. We also find that charge‐compatible and size‐complementary cations (Cd 2+ or Sn 4+ ) can induce an abrupt phase transition from super‐sodalite to super‐diamond, also with unprecedented trimetallic T2 clusters. For In 3+, which is dual‐complementary (charge and size), a gradual phase transition is observed with increasing In 3+ amount. Furthermore, by controlling the cluster composition, tunable band gaps can be realized. These materials show promising properties such as high CO2 uptake (4.32 mmol cm −3, 298 K, 1 bar) and high photocatalytic activity. Abstract : Smart dopants can improve morphology and selectively enhance relative phase stability, in addition to tune compositions and band structures, as shown here in a family of zeolite‐type chalcogenides. New trimetallic T2 clusters are synthesized for the first time in zeotype structures. These materials with different chemical compositions show tunable band gap, gas adsorption and photocatalytic H2 production properties.